2013
DOI: 10.1155/2013/376247
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Alleviation through Optimizing the Marketing of Garcinia kola and Irvingia gabonensis in Ondo State, Nigeria

Abstract: The paper examines poverty alleviation through optimizing the marketing of Garcinia kola and Irvingia gabonensis in Ondo State, Nigeria. Data for this study were collected using structured questionnaire. Two categories of pretested structured questionnaires were used to obtain information from the respondents (farmers and the marketers of the species). Data analysis was done using descriptive analysis, and Student t-test was used to compare the income generated by the producers and the marketers of the fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Socio-economic characteristics of bitter kola marketers: Table 1 shows the socio-economic characteristics of bitter kola marketers in Akwa Ibom State. The Table reveals that the mean age of bitter kola marketers in the study area was 37 years which agrees with [14] who reported that majority of the bitter kola marketers in Nigeria were within the age range of 20-50 years. About 61.7% of the respondents were females and majority of them (58.3%) were married.…”
Section: Methodssupporting
confidence: 86%
“…Socio-economic characteristics of bitter kola marketers: Table 1 shows the socio-economic characteristics of bitter kola marketers in Akwa Ibom State. The Table reveals that the mean age of bitter kola marketers in the study area was 37 years which agrees with [14] who reported that majority of the bitter kola marketers in Nigeria were within the age range of 20-50 years. About 61.7% of the respondents were females and majority of them (58.3%) were married.…”
Section: Methodssupporting
confidence: 86%
“…Farmers obtain appreciable income and livelihood support from sale of fruits/seeds of the species. Results from this study as well as Agbelade and Onyekwelu (2013) showed that farmers and/or traders in the study area obtained mean annual income of between 300 and 1300 US$ from sale of C. albidum, I. gabonensis and G. kola fruits/seeds. Ayuk et al (1999a) showed that G. kola nuts harvesting can contribute up to 60 US$ to family annual income in Cameroon, while Franzel et al (1996) and Ayuk et al (1999b) noted that harvest of I. gabonensis fruits and seeds can contribute between 40 and 93 US$ to annual household income, which are very low compared with the figures reported in this study.…”
Section: Discussionmentioning
confidence: 69%
“…Annual income increased as one moves from farm gate to urban market ( Figure 2). Detailed income generated by farmers and traders from sale of the three species has been presented by Agbelade and Onyekwelu (2013). Most of the traders traded only one of the species, only few traders were engaged in the marketing of the fruits/seeds of more than one species at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…This precipitates quick transportation and sale of bush mango during lower prices [13]. Bush mango kernel quantities over the last five years have been increasing [13] and its marketing is a female oriented enterprise with about 90% women involved in the trade [14]. The main determinants of the selling price for bush mango kernels were the cost price of the commodity and transportation cost.…”
Section: Introductionmentioning
confidence: 99%